Bibliometric Analysis of Physics Learning Studies: Focus on Differentiation and Problem Solving Strategies - Rahmatta Thoriq Lintangesukmanjaya; Binar Kurnia Prahani; Dwikoranto; Dea Ramadhana Zsa Zsa Alifah; Sallimah binti Hj Mohd Salleh; Iwan Wicaksono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: Analyzing the potential of differentiation learning to create problem-solving strategies is essential. This aims to evaluate the shortcomings and advantages to become findings in future research. Method: This research was conducted using bibliometric analysis and systematic review methods. The use of these two methods is carried out in order to obtain in-depth analysis through qualitative and quantitative data. Results: Based on the research that has been conducted, it is known that the trend of physics learning research with a differentiation approach through problem-solving strategies in educational articles over the past 10 years has continued to increase every year. Novelty: In accordance with the findings of the bibliometric analysis, it was obtained that one of the experience-based learning that can be integrated with the differentiation approach is the PBL (Problem Based Learning) learning model. It is recommended for future researchers to integrate PBL learning in physics with a differentiation approach as a strategy to improve problem-solving skills according to the global trend in adapting innovative learning through interactive methods.